Studi tentang pola produksi alfalfa tropis (Medicago sativa L.) - Rini Dwi Wahyuni; Siti Nurul Kamaliyah (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2009)
Abstract The research aims to determine the growth pattern of alfalfa in the tropical region, which later can be used as a source of information for the people needed. Research methods used are experimental; the data acquired during the 90 days was showed in a graph and then analyzed using regression analysis with two variables, namely independent variables (cutting age) and dependent variables (the nutritive value, height of plants, and production of dry matter (DM), organic matter (OM), and crude protein (CP)). The growth pattern of alfalfa in the range 20 to 90 days was quadratic, with the equation of y= -0.0092x2 + 1.6113x – 19.257. At that range of time the alfalfa was still in vegetative growth phase. With increasing age of cutting, the alfalfa chemical compositions of DM and OM increased, but the content of CP decreased.While the production of DM, OM, and CP increased with increasing cutting age. Key words: nutrition, growth, alfalfa, tropics